Deformation and evolution of life in crystalline materials : an integrated creep-fatigue theory - Wu, Xijia, 1958- (Boca Raton, FL : CRC Press, 2019)
This book walks you through the fundamental deformation and damage mechanisms. It lendsthe readerthe key to open the doors into the maze of deformation/fracture phenomena under various loading conditions. Furthermore it provides the solution method to material engineering design and analysis problems, for those working in the aerospace, automotive or energy industries. The book introduces the integrated creep-fatigue theory (ICFT) that considers holistic damage evolution from surface/subsurface crack nucleation to propagation in coalescence with internally-distributed damage/discontinuities.
"A science publishers book."
OCLC-licensed vendor bibliographic record.
Keywords: Crystallography; Crystal growth; Crystals; Crystals -- Plastic properties; Dislocations in crystals; Minerals; SCIENCE / Energy; SCIENCE / Mechanics / General; SCIENCE / Physics / General; SCIENCE / Chemistry / General; SCIENCE / Life Sciences / General; TECHNOLOGY / Material Science